2018
DOI: 10.1177/0018720818781196
|View full text |Cite
|
Sign up to set email alerts
|

Human Performance Deterioration Due to Prolonged Wakefulness Can Be Accurately Detected Using Time-Varying Spectral Analysis of Electrodermal Activity

Abstract: This can be used to detect the adverse effects of prolonged wakefulness on human performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 51 publications
5
18
1
Order By: Relevance
“…By the end of the 24 h, the performance exhibited a recovery, which suggests the ANS is re-activated. This has also been observed in the recovering performance reported in previous studies and is thought to be related to the circadian rhythm [11,44,45].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…By the end of the 24 h, the performance exhibited a recovery, which suggests the ANS is re-activated. This has also been observed in the recovering performance reported in previous studies and is thought to be related to the circadian rhythm [11,44,45].…”
Section: Discussionsupporting
confidence: 83%
“…KNN and LSVM exhibited a reduction in accuracy on the classification between 20 and 22 h. Previous studies have found a reduction in performance at 22 h of wakefulness [11,44,45]. The low accuracy suggests that the activation of the ANS was diminished (or at least different) after 20 h of wakefulness, compared to the trials in normal conditions (first trials).…”
Section: Discussionmentioning
confidence: 81%
“…To evaluate this, we have employed a simple yet robust test that requires the subject to maintain response inhibition and reactivity. This information from the neurophysiological measures of the oscillatory activity of the brain can complement physiological measures used in studies focused on autonomic reactions (Posada-Quintero et al, 2017, 2018), to predict the effect of sleep deprivation on human autonomic response and performance.…”
Section: Introductionmentioning
confidence: 99%
“…Our choice of 20 subjects allows greater than 95% confidence interval to observe a significant effect (p < .05 ;Faul, Erdfelder, Lang, & Buchner, 2007;Sundelin et al, 2013). Furthermore, this sample size is sufficient to detect a correlation of at least 0.8 between PVT and facial indices at the 0.05 level of significance (Dorrian, Rogers, & Dinges, 2005;Posada-Quintero et al, 2018;Zar, 1999).…”
Section: Participantsmentioning
confidence: 98%
“…To address these issues, researchers have been working to develop effective methods to detect and/or predict decrements in performance due to prolonged wakefulness before costly mistakes are made. These efforts include vocal features, electrodermal activity signals, and heart rate variability (McGlinchey et al, 2011;Posada-Quintero, Bolkhovsky, Qin, & Chon, 2018;Sloboda et al, 2018). However, vocal features are not easy to document in noise environment, and the other biosignal methods are limited in that they are sensitive to motion artifacts, expensive, and require electrodes to be attached to the skin/body.…”
mentioning
confidence: 99%